Insiders, Outsiders, and the Constructed Limits to Social Rights in EU Law - Alezini Loxa (European Papers)
(Series Information) European Papers - A Journal on Law and Integration, 2025 10(1), 163-190 | Article | (Table of Contents) 1. Introduction. – 2. The limitations of social rights of EU migrants. – 2.1. Secondary law. – 2.2. The consolidation of the limitations in the case law. 3. The differentiated social rights of non-EU migrants. – 3.1. Accepted limitations to social rights of non-EU migrants. – 3.2. The judicial review of the limitations. – 4. Combining the approaches? – 4.1. The potential for Charter rights to guide both frameworks – 4.2. Financial solidarity dictating the outer limits to social rights for all migrants. | (Abstract) This paper engages with limitations to social rights for different categories of migrants under EU law. By looking at how EU law construes accepted limitations to social rights and how the Court of Justice reviews such limitations, the paper suggests that there is room for different interpretation of limitations to social rights under secondary law in view of a more coherent understanding of their function under EU law. Specifically, the paper maps the accepted limitations to the social rights of EU migrants, long-term residents, and regular migrants. By reviewing the justifications put forward behind all the accepted limitations to social rights, the paper argues that the function served by limitations to social rights is uniform across all categories of migrants: that is avoiding the presumed negative effects of migration to national redistributive mechanisms. At the same time, the Court follows different paths of review depending on the status of the migrants (EU or non-EU). While some differentiation in the approach followed by the Court is justified, the paper argues that there is room for evolution in judicial review by combining elements of the judicial approach for both EU and non-EU migrants in light of the social objectives of the EU under Article 3 TEU and the Charter. The paper presents the potential of this combination not as a groundbreaking shift in the functional approach followed by EU law to social rights, but rather as a limited change that can bring about more extensive protection of social rights for all migrants.